The Prevalence and Correlates of Physical and Sexual Violence Affecting Female Sex Workers in Swaziland. Issue 17 (September 2018) - Berger, Blair O.; Grosso, Ashley; Adams, Darrin; Ketende, Sosthenes; Sithole, Bhekie; Mabuza, Xolile S.; Mavimbela, Mpumelelo J.; Baral, Stefan
Female sex workers (FSW) have a heightened vulnerability to violence and negative sexual/reproductive health outcomes. Limited research has examined how experiencing physical and sexual violence (PSV) mediates risk for poor health outcomes among FSW in Swaziland. The present analyses aim to contribute to literature linking violence with poor health outcomes, high-risk behaviors, and reduced health service-seeking among FSW. Data were analyzed from a cross-sectional study conducted in Swaziland between July and September 2011 with 325 adult women who reported exchanging sex for money, goods, or favors in the last 12 months, recruited through respondent-driven sampling (RDS). Logistic regression was used to assess the relationship between PSV and ancillary violence/abuse exposures, risk behaviors, and sexual/reproductive and mental health outcomes. PSV was conceptualized as either ever having been beaten up as a result of selling sex or ever being forced to have sex since the age of 18, or both. Prevalence of PSV in this sample was 59.0% in crude estimation, and 48.4% (95% confidence interval [CI]:[39.2, 57.6]) with RDS weighting. Separate RDS-weighted estimates of being beaten up as a result of sex work and ever being forced to have sex were 32.4% (95%CI=[24.4, 40.4]) and 33.1% (95%CI =[25.0, 41.2%]), respectively. Experiencing PSV was associated with being blackmailed (adjusted odds ratio [aOR]= 1.93, 95%CI= [1.07, 3.52]), non-injection drug use in the last 12 months (aOR= 1.84, 95%CI= [1.02, 3.33]), and feeling afraid to seek health services as a result of selling sex (aOR = 1.74, 95%CI= [1.01, 2.99]). Given these findings, violence prevention strategies should be prioritized in programs that address Swazi FSW health, empowerment, and safety.